2018
DOI: 10.3389/fmicb.2018.00794
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Food-Grade TiO2 to Commensal Intestinal and Transient Food-Borne Bacteria: New Insights Using Nano-SIMS and Synchrotron UV Fluorescence Imaging

Abstract: Titanium dioxide (TiO2) is commonly used as a food additive (E171 in the EU) for its whitening and opacifying properties. However, a risk of intestinal barrier disruption, including dysbiosis of the gut microbiota, is increasingly suspected because of the presence of a nano-sized fraction in this additive. We hypothesized that food-grade E171 and Aeroxyde P25 (identical to the NM-105 OECD reference nanomaterial in the European Union Joint Research Centre) interact with both commensal intestinal bacteria and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 66 publications
(103 reference statements)
3
42
0
Order By: Relevance
“…6). These observations are similar to those of bacteria exposed to TiO 2 , which reportedly causes bacterial cell rupture 18 . However, the exact mechanism how ticagrelor kills C. difficile remains to be further explored.…”
Section: Discussionsupporting
confidence: 87%
“…6). These observations are similar to those of bacteria exposed to TiO 2 , which reportedly causes bacterial cell rupture 18 . However, the exact mechanism how ticagrelor kills C. difficile remains to be further explored.…”
Section: Discussionsupporting
confidence: 87%
“…Commonly used nanomaterials, such as TiO 2 NMs, can also change the composition and metabolic activity of micro biota in coculture system of TiO 2 NMs (22 nm) and eight bacterial strains including both Grampositive and Gram negative bacteria. [117] Specifically, TiO 2 NMs increased the ratio of Lawsonia and Hyphomicrobium at genus level. Correlation analysis demonstrated that Lawsonia was associated with the generation of ROS while Hyphomicrobium showed an oppo site effect on that, indicating that nanomaterials can trigger oxidative stress through modulating the structure of gut microbiota.…”
Section: Effects Of Nanomaterials On Gut Microbiotamentioning
confidence: 95%
“…Nevertheless, oral bioavailability studies in rodents and humans clearly showed very limited systemic absorption of TiO 2 (0.1 to 0.6% of the initial dose, respectively) [118,119]. This finding indicates that at least 99% of the ingested TiO 2 matter accumulates in the lumen of the gut with the commensals in permanent contact with the particles, especially due to repeated exposure, with the potential for alterations in the growth profiles of bacteria as shown in vitro for E171 [8]. Mice exposed for one week to TiO 2 -NPs at a relevant dose for humans (2.5 mg/kg bw/d) did not reveal any changes in the faecal microbiota composition [107].…”
Section: Impacts Of Nano-silver and Titanium Dioxidementioning
confidence: 98%
“…Following ingestion, NPs interact with a complex gastrointestinal (GI) environment. The non-absorbed fractions of foodborne mineral NPs (or their ionic forms for soluble compounds, such as Ag and ZnO) are accumulated in the intestinal lumen as a result of daily consumption, and can directly interact with the intestinal microbiota colonizing the gut lumen as well as the mucus layer lining the epithelial surface [7][8][9]. A portion of the NPs then translocate through the epithelial barrier and are possibly captured by the intestinal immune cells (e.g., macrophages and dendritic cells), before reaching systemic circulation.…”
Section: Introductionmentioning
confidence: 99%